THE MANAGEMENT PROCESS AND THE ADDED VALUE OF THE SPORTS INDUSTRY - Chantharat, Niwat; Chantharat, Sumana (วารสาร มจร พุทธปัญญาปริทรรศน์, 2024)
The management process of sports competition events acts as an intermediary in driving the supply chain in the sporting industry because it involves the process of hiring sports personnel and purchasing equipment from other businesses in the sports industry. This leads to the expansion of the sports industry and groups sports competition management which is an added value for the entire sports industry. It is the beginning of the value of sports management. The competition must have a clear competition management process; additionally, it must pay attention to the management of sports resources which is in line with the management of sports competitions in order to add value to the sports industry. This article explains the relationship between sports resources. It focuses on sporting fame, technology and innovation in sports, sports project management skills and national sports competition management guidelines. The guidelines lead to the process of assessing the sports competition environment and the results of sports competition events that add long-term value to sports industry in Thailand. The finding found that the sports resources and national sporting events management approaches influence adding value to the sporting industry, which will present an approach that businesses in the sporting industry can apply to achieve efficiency in the management of total sporting resources. To have clear indicators of success in business operations, including assessing projects after organizing the competition and moving towards the goal of creating added value that brings results that will create stability for the business.